2010
DOI: 10.1002/jbt.20354
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of lipoic acid and selenium against cadmium‐induced biochemical alterations in testicular steroidogenesis

Abstract: Exposure to toxic metals including cadmium has become an increasingly recognized source of illness worldwide. Cadmium (Cd(2+) ) is one of the environmental pollutants affecting various tissues and organs including testis. The protective effect of lipoic acid and selenium on Cd(2+) -induced testicular damage was investigated. Accordingly, male Wistar rats were allocated into four groups (n = 8; each). Gp I: (control), whereas the other 3 groups received CdCl(2) (2 mg/kg, i.p. for 28 days) alone or in combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 57 publications
2
19
0
1
Order By: Relevance
“…In harmony with the current findings, it was documented that selenium reduced the oxidative stress, endocrine disorder and apoptosis in the rat testes [85,86] . It was declared that the mechanism of chemoprotection of selenium may be related to its properties as antioxidant besides its ability to hinder with pathways of DNA repair [87] .…”
Section: Discussionsupporting
confidence: 87%
“…In harmony with the current findings, it was documented that selenium reduced the oxidative stress, endocrine disorder and apoptosis in the rat testes [85,86] . It was declared that the mechanism of chemoprotection of selenium may be related to its properties as antioxidant besides its ability to hinder with pathways of DNA repair [87] .…”
Section: Discussionsupporting
confidence: 87%
“…Grotto et al [39] reported that in rats chronically exposed to low levels of methylmercury, selenium co-administration showed a significant reduction in methylmercury-induced genotoxicity, reestablished glutathione peroxidase activity and reduced and Histochemical Alterations in Prostate of Albino Rats DNA damage. Selenium reduced the cadmium induced histopathological changes in testes of rat, oxidative stress, endocrine disorder and apoptosis [40,41]. On the contrary, Adesiyan et al [42] reported that selenium had no protective effects against atrazine-induced biochemical alterations in testis and epididymis except testicular lactate dehydrogenase.…”
Section: Figurementioning
confidence: 99%
“…Activation of NADPH oxidase, as well as mitochondrial damage, is believed to play a role in Cd-induced oxidative stress [19,43,87,88]. Other nutraceutical antioxidants, such as astaxanthin, lipoic acid, melatonin, Nacetylcysteine, and phase II inducers, may likewise have potential for mitigating Cd's pathogenic impact [89][90][91][92][93][94][95][96][97][98][99] -though it should be acknowledged that oxidative stress is unlikely to be the only mechanism mediating Cd's adverse effects. The researchers who reported high Cd levels in vegans, also note that whole plant-based foods tend to rich in phytochemical antioxidants which might to some degree offset the toxic impact of Cd [46].…”
Section: Supplemental Antioxidants As Antidotes To Cadmium Toxicitymentioning
confidence: 99%